Paul the Rabbi of Messianic Judaism Reading the Antioch Incident within Judaism as an Irreducibility Story - Willitts, Joel (2016)
This article presents a reconsideration of the Antioch incident of Gal 2:11-21, arguing that Paul's issue with Peter and the Jewish believers in Jesus in Antioch was not theological, but halakhic, that is, how to live as a Messianic Jew particularly in relationship to Gentile Messiah believers. Paul's use of the story from his days in Antioch analogically served his purpose among Galatian Gentile Messiah-believers by both asserting his apostolic authority and by instructing them to resist any attempt to embrace an ethnically Jewish identity in Messiah. Such an interpretation of this significant Pauline crux derives from two factors. First, the study assumes that Paul was still firmly within the diverse Judaism of the late Second Temple period. Thus, the study considers the meaning of the Antioch incident within the framework of a "Paul within Judaism." Second, the study applies narratology to the interpretation of Gal 2:11-21. Taking notice of the storied structure of the passage, consisting of a beginning, middle, and end, this article reads the parts of the story in relationship to the whole. The consequence of these two factors is (1) a plausible historical interpretation of the events of Antioch, albeit from Paul's perspective, and (2) a reading of the passage that is sensitive to its literary character.
Keywords: Jewish Diaspora; Jewish foods; Jewish Law; Jewish peoples; Judaism; Narratives; Rabbis; Temples; Torah